Synthesis and characterization of metal oxides supported keggin type polyoxometalate Rb2K2[-H2SiV2W10O40].nH2O - Eiffel Ostan Jeski Gultom; Aldes Lesbani (Science and Technology Indonesia, 2017)
Synthesis of material based on polyoxometalate Rb2K2[γ-H2SiV2W10O40].nH2O with SiO2, TiO2, ZrOCl2, and TaCl5 was carried out to form Rb2K2[γ-H2SiV2W10O40].nH2O-SiO2, Rb2K2[γ-H2SiV2W10O40].nH2O-TiO2 Rb2K2[γ-H2SiV2W10O40].nH2O-ZrOCl2 and Rb2K2[γ-H2SiV2W10O40].nH2O-TaCl5. Materials from preparation were characterized through functional group analysis using FT-IR spectrophotometer, crystallinity analysis using XRD and surface photograph analysis using SEM. The results show that material Rb2K2[γ-H2SiV2W10O40].nH2O was successfully loaded with SiO2, ZrOCl2 and TaCl5. Based on SEM photo Rb2K2[γ-H2SiV2W10O40].nH2O-TiO2 and Rb2K2[γ-H2SiV2W10O40].nH2O-ZrOCl2 were the best material from preparation base on the homogeneity particle distribution. The FT-IR spectrum shows specific wavenumber for nanomaterial Rb2K2[γ-H2SiV2W10O40].nH2O-TiO2 in the range 455-910 cm-1 and Rb2K2[γ-H2SiV2W10O40].nH2O - ZrOCl2 in the range 393.48-1404 cm-1. XRD pattern for material Rb2K2[γ-H2SiV2W10O40].nH2O-TiO2 and Rb2K2[γ-H2SiV2W10O40].nH2O-ZrOCl2 show there is a difference between polyoxometalate Rb2K2[γ-H2SiV2W10O40].nH2O, TiO2 and ZrOCl2. SEM photo analysis of Rb2K2[γ-H2SiV2W10O40].nH2O-TiO2 and Rb2K2[γ-H2SiV2W10O40].nH2O-ZrOCl2 showed that material polyoxometalate with support has a diameter size of particle above 100 nm. Keywords: Rb2K2[γ-H2SiV2W10O40].nH2O, polyoxometalate, SiO2, TaCl5, TiO2, ZrOCl2.